Sociolinguistic factors influencing chinese parent's choice of language of instruction for their children's primary education - Lee, Diana Phooi Yan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Parents’ choice of school language of instruction is influenced by individual, group and societal factors. The study examined the sociolinguistic factors that affect the Chinese parents’ choice of language of instruction for their children’s primary education using the Theory of Planned Behaviour. The specific objectives of the study were to: (1) compare the parents’ attitude towards school language of instruction for Mandarin- and Malay-medium primary schools; (2) compare the influence of subjective norm on the choice of Mandarin- and Malay-medium primary schools; (3) compare the parents’ perceived behavioural control on the choice of Mandarin- and Malaymedium primary schools; (4) compare the strength of ethnic identity of Chinese parents with children in Mandarin- and Malay-medium primary schools and its effect on their choice of language of instruction for their children’s primary education; and (5) determine the relative importance of factors influencing parents’ choice of language of instruction for their children’s primary education. A questionnaire survey of 400 Chinese parents with children in Primary One was conducted in Kuching, Sarawak. The survey involved 200 parents with children in Malaymedium primary schools and 200 parents with children in Mandarin-medium primary schools. The questionnaire had sections on: demographic details, Ethnic Identity Scale, Familial Ethnic Socialisation Measure, Self-esteem Scale, attitudes towards school, subjective norm, perceived behavioural control and parents’ intention to send their children to Mandarin- and Malay-medium primary schools. The results for the two groups of parents were compared using means and tvii tests. A comparison of the parents’ attitude towards school language of instruction showed that the parents who sent their children to Mandarin- and Malay-medium primary schools perceived that the school of their choice equipped their children with good academic qualifications, future prospects and also desirable personal characteristics (diligence, racial tolerance and openmindedness). In addition to these, the Mandarin-medium school parents perceived that Mandarinmedium primary schools provided their children with more exposure towards Chinese language and culture than Malay-medium primary schools. Next, a comparison of the influence of subjective norm (or the social network) on the choice of Mandarin- and Malay-medium primary schools showed that the Malay-medium school parents referred to their spouse when choosing the primary school for their children whereas the Mandarin-medium school parents were influenced by their social network. In regards to the perceived behavioural control, both groups of parents have control over their choice (i.e., they would send their children to the school that they preferred) with the former having better control than the latter on fees and choice of school in a convenient location. Subsequently, a comparison of the strength of ethnic identity between the two groups of Chinese parents showed that they have positive identification with their Chinese identity, but Mandarin-medium school parents have a stronger Chinese identity than the Malay-medium school parents. Finally, by using the Theory of Planned Behaviour and regression analysis, the relative importance of sociolinguistic factors influencing choice of school language of instruction were determined. The results revealed that attitude towards school language of instruction and the perceived behavioural control were the main factors influencing the decision of both groups of parents. In addition to these two factors, subjective norm also influenced the Malay-medium school parents’ choice of school language of instruction. The parents’ strength of Chinese identity was found to have low predictive power in relation to other factors in viii determining choice of school language of instruction for both groups of parents. The results show that the factors with high predictive power were those directly related to the choice of the school, whether it is Mandarin or Malay as the language of instruction. These findings have implications on strategies that schools may use to increase student enrolment. In terms of theoretical contribution, the study has shown that with the use of the Theory of Planned Behaviour as a theoretical framework, the relative importance of factors influencing choice of school language of instruction can be established, leading to a better understanding of parental school choice.